2016
DOI: 10.1016/j.rbmo.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Corifollitropin alfa versus recombinant follicle-stimulating hormone: an individual patient data meta-analysis

Abstract: A meta-analysis was conducted of individual patient data (n = 3292) from three randomized controlled trials of corifollitropin alfa versus rFSH: Engage (150 µg corifollitropin alfa n = 756; 200 IU rFSH n = 750), Ensure (100 µg corifollitropin alfa n = 268; 150 IU rFSH n = 128), and Pursue (150 µg corifollitropin alfa n = 694; 300 IU rFSH n = 696). Women with regular menstrual cycles aged 18-36 and body weight >60 kg (Engage) or ≤60 kg (Ensure), or women aged 35-42 years and body weight ≥50 kg (Pursue), receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 12 publications
1
18
0
2
Order By: Relevance
“…One of the limitations of this study could lie in assuming a similar effectiveness for all comparators. However, assuming similar effectiveness between corifollitropin alfa and rFSH is supported by other studies ( Devroey et al, 2009 , Obruca et al, 2010 ) and recent meta-analyses ( Fensore et al, 2015 , Griesinger et al, 2016 , Pouwer et al, 2016 ). As regards comparing similar effectiveness between different rFSH, Gizzo et al (2016) considered follitropin alfa biosimilar_B to be less effective than follitropin alfa, which is in contrast to the findings of this study.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…One of the limitations of this study could lie in assuming a similar effectiveness for all comparators. However, assuming similar effectiveness between corifollitropin alfa and rFSH is supported by other studies ( Devroey et al, 2009 , Obruca et al, 2010 ) and recent meta-analyses ( Fensore et al, 2015 , Griesinger et al, 2016 , Pouwer et al, 2016 ). As regards comparing similar effectiveness between different rFSH, Gizzo et al (2016) considered follitropin alfa biosimilar_B to be less effective than follitropin alfa, which is in contrast to the findings of this study.…”
Section: Discussionmentioning
confidence: 62%
“…In this study, the cost per treatment outcome based on the number of oocytes recovered was lower with corifollitropin alfa than with rFSH for both the overall population as well as age subgroups. This reduction could be greater if the results from a recent meta-analysis, highlighting the greater capacity of corifollitropin alfa to generate oocytes, are taken into consideration ( Fensore et al, 2015 , Griesinger et al, 2016 , Pouwer et al, 2016 ). Cruz et al (2017) carried out a cost-effectiveness analysis on egg donors who received treatment with corifollitropin alfa, rFSH or HP-HMG, expressing the results based on the cost per recovered oocyte and per metaphase 2 oocyte, without encountering statistically significant differences between the treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that a single dose of corifollitropin alfa for the first 7 days of stimulation is similarly effective as daily injected rFSH. 36 Additionally, a Cochrane review including six randomized controlled trials, with a total of 3,753 patients, resulted in no significant differences between patients treated with the long-acting FSH and daily rFSH. From the analyzed data it was concluded that the long-acting FSH is a safe treatment and equally effective compared to daily FSH, but its efficacy in the treatment of hyper or poor responder women is still to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Although experience with corifollitropin alfa is still incipient when compared to other gonadotropins, several studies have been carried out in recent years to assess its efficacy and compare it against traditional ovarian induction regimens ( Devroey et al. , 2009 ; Mahmoud Youssef et al , 2012 ; Kolibianakis et al , 2015 ; Griesinger et al. , 2016 ).…”
Section: Introductionmentioning
confidence: 99%